História da ciência em livros didáticos de Química aprovados no PNLEM/2018 - (:unkn) unknown (Universidade Federal do Pampa, 2018)
Research in the area of Science Teaching has found that the textbook has a direct influence on teaching and learning, being one of the main guides in the planning of classes by educators. Several authors, on the other hand, argue that the understanding of the History of Science contributes to the learning of scientific concepts, however, they point out that the lack of adequate bibliographical sources, coupled with the lack of specific training, are obstacles to its use in the classroom. In this sense, the present work seeks to investigate how the History of Science has been worked on in the textbooks of Chemistry, in order to assist the teacher in its implementation in teaching and in parallel to point out problems and raise questions relevant to future adaptations. To this purpose, the six collections of Chemistry textbooks (Teacher's Manual), approved by the National Program of the Didactic Book for High School (PNLEM / 2018), will be analyzed. As a data analysis technique, the Content Analysis of Bardin (2011) was used, constituting itself as a qualitative and quantitative research. The categories of analysis used to evaluate the contents related to the History of Science in these school textbooks were adapted from the instrument developed by Leite (2002), in which some modifications were made in order to adapt it to the research objectives. As a result it is pointed out that there is a reasonable frequency of the History of Science in most of the school textbooks analyzed, however, lack of articulation with the presented concepts turns it into an isolated information, being used as a complement to the content.
Keywords: História da Ciência; Livro Didático; Ensino de Química; History of Science; Textbook; Chemistry teaching; CNPQ::CIENCIAS EXATAS E DA TERRA